High Altitude Ramsar Sites of Nepal: Criteria and Future Ahead - Karki, Jhamak B; Siwakoti, Mohan; Pradhan, Neera Shrestha (The Initiation, 2010)
DOI: 10.3126/init.v1i0.2674 The Initiation Vol.1 2007 p.9-15